Architecture of TOI-561 planetary system - Piotto, G.; Davies, M.B.; Korth, J.; Wolf, S. (Monthly Notices of the Royal Astronomical Society, 2024)
We present new observations from CHEOPS (CHaracterising ExOPlanet Satellite) and TESS (Transiting Exoplanet Survey Satellite) to clarify the architecture of the planetary system hosted by the old Galactic thick disc star TOI-561. Our global analysis, which also includes previously published photometric and radial velocity data, incontrovertibly proves that TOI-561 is hosting at least four transiting planets with periods of 0.44 d (TOI-561 b), 10.8 d (TOI-561 c), 25.7 d (TOI-561 d), and 77.1 d (TOI-561 e) and a fifth non-transiting candidate, TOI-561f with a period of 433 d. The precise characterization of TOI-561's orbital architecture is interesting since old and metal-poor thick disc stars are less likely to host ultrashort-period super-Earths like TOI-561 b. The new period of planet -e is consistent with the value obtained using radial velocity alone and is now known to be 77.14399 ± 0.00025 d, thanks to the new CHEOPS and TESS transits. The new data allowed us to improve its radius (Rp = 2.517 ± 0.045 R⊕ from 5 per cent to 2 per cent precision) and mass(Mp = 12.4 ± 1.4 M?) estimates, implying a density of ρp = 0.778 ± 0.097 ρ⊕. Thanks to recent TESS observations and the focused CHEOPS visit of the transit of TOI-561 e, a good candidate for exomoon searches, the planet's period is finally constrained, allowing us to predict transit times through 2030 with 20-min accuracy. We present an updated version of the internal structure of the four transiting planets. We finally performed a detailed stability analysis, which confirmed the long-term stability of the outer planet TOI-561 f. © 2024 The Author(s). Published by Oxford University Press on behalf of Royal Astronomical Society.
Keywords: ephemerides; planets and satellites: dynamical evolution and stability; planets and satellites: fundamental parameters; planets and satellites: interiors; techniques: photometric; techniques: radial velocities; Astronomical satellites; Exoplanets; Interplanetary flight; Interplanetary spacecraft; Orbits; Photometers; Tropics; Disc stars; Ephemeride; Exo-planets; Planetary system; Planets and satellites: dynamical evolution and stabilities; Planets and satellites: fundamental parameters; Planets and satellites: interiors; Techniques: photometric; Techniques: radial velocities; Thick discs; Stars